The effectiveness of 3 types of physical traffic calming device : which is most relevant at reducing traffic speeds - Wong, Leong Sing. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The demand by the public to reduce traffic volumes and speeds in their restricted areas has necessitated traffic engineers and the government authority to come out with effective traffic calming strategies. Physical traffic calming devices are often installed to overcome traffic flow problems in restricted areas but the effectiveness of such devices is largely dependent on the size and shape of such devices. As such, the project aims to determine the most effective physical traffic calming device at reducing vehicular speeds from 3 types of such devices, namely speed bump, round-top speed hump and speed table which were installed in 3 different locations as well as to evaluate the relevancy of installation of such devices. The methodology contained in the project illustrates method of sampling from populations of vehicles on the streets where the devices were installed and describes procedures of conducting spot-speed studies using speed radar gun to analyze the relationship between vehicular speeds and the devices. Engineering review and analysis of all data were done through traffic volume studies, spot-speed studies, regression studies, questionnaires and interviews. From the project, although speed table at Padungan Street proves to be most effective at reducing critical speeds (-6.82 kph) if compared to speed bump in the compound of Universiti Malaysia Sarawak (UNIMAS) campus (-2.40 kph) and round-top speed hump on Lane 8A, Bayor Bukit Road (-4.70 kph), the amount of vehicular speed reduction for all the devices are rather small (less than 10 kph). This creates an issue on the suitability of installing such devices in their respective areas. Regression analysis performed in the project indicates that as the height and width of the devices increase, the entry speeds decrease. This shows that drivers are reasonably influenced by the dimensions of the devices. However, there is a lack of association between the 15th percentile entry speed with respect to the height (R2 = 0.3697) and width (R2 = 0.4942) of the devices. This may be due to differing drivers' attitudes and speed preferences in selecting the 15`h percentile entry speed at 15 m before the devices. Relevancy analysis through questionnaires distributed among 50 responders at locations where such devices were installed reviews that all the devices are reasonably accepted with speed bump mostly accepted (80 % rate of approval), followed by speed table and round-top speed hump with 76 % and 62 % rate of approval respectively.